2021
DOI: 10.3390/pharmaceutics13071054
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Temoporfin Distribution in Blood by β-Cyclodextrin Nanoshuttles

Abstract: Photodynamic therapy represents a more targeted and less invasive alternative cancer treatment to traditional modalities. Temoporfin, as with many photosensitizers, is given by injection into a vein, and its subsequent fate is largely determined by the binding to plasma proteins and interaction with endothelial and blood cells. Thus, it is essential to be able to control and to alter the biodistribution of temoporfin in blood. In the present study, we evaluated the effect of co-administration of temoporfin wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…With mTHPP it was shown that covalently linked PS-b-cyclodextrin compounds had better PDT activity in vitro against glioblastoma cells compared to inclusions complexes (369). The affinity of temoporfin to cyclodextrin could also be influenced by methylation of the cyclodextrin carrier (129,365). Temoporfin and b-cyclodextrins have also been combined with liposomes as a second carrier to obtain 'drug-in-cyclodextrin-in-liposome' nanoparticle systems.…”
Section: Cyclodextrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…With mTHPP it was shown that covalently linked PS-b-cyclodextrin compounds had better PDT activity in vitro against glioblastoma cells compared to inclusions complexes (369). The affinity of temoporfin to cyclodextrin could also be influenced by methylation of the cyclodextrin carrier (129,365). Temoporfin and b-cyclodextrins have also been combined with liposomes as a second carrier to obtain 'drug-in-cyclodextrin-in-liposome' nanoparticle systems.…”
Section: Cyclodextrinsmentioning
confidence: 99%
“…In some of these animal investigations with temoporfin detection via fluorescence, the window-chamber tumor model has successfully been used (288,(302)(303)(304). The detection of temoporfin by fluorescence spectroscopy methods as well as absorption spectroscopy has also proven to be a valuable or perhaps even the standard tool in pharmaceutical formulation development, allowing to follow the active substance molecule when the pharmaceutical formulation interacts with body fluids and is distributed to body compartments (129,171,221,293,365,367,392). Moreover, changes in fluorescence behavior of temoporfin and changes in its absorption spectrum can be used to characterize the immediate surroundings of the photosensitizer (366,368,393,554).…”
Section: Dosimetry and Detectionmentioning
confidence: 99%